2016
DOI: 10.1111/jace.14471
|View full text |Cite
|
Sign up to set email alerts
|

Increased electrical conductivity and the mechanism of samarium‐doped ceria/Al2O3 nanocomposite electrolyte

Abstract: To further enhance the electrical conductivity of doped ceria, the samarium‐doped ceria (SDC)/Al2O3 nanocomposites were prepared through sintering the coprecipitated powders in 1100°C‐1300°C. The grain sizes of all composites are less than 100 nm and decrease with alumina addition. Besides the main phases of SDC and Al2O3, the SmAlO3 can precipitate in the composites if sintered at higher temperatures or for longer dwell time. The deviations of SDC diffraction peak positions demonstrate the solid solution of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Compared with CoFeP, the discharge capacity of the FeP electrode decreases significantly from the first cycle, and the capacity is decreased to only 165.9 mA h g −1 after 87 cycles. The reason for the large difference in capacities for CoFeP and FeP is that the Co doping into FeP boosts the electronic conductivity of electrode, and the unique hollow structure affords more active sites and provides a faster kinetics . Figure b shows the rate capabilities of the FeP and CoFeP electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with CoFeP, the discharge capacity of the FeP electrode decreases significantly from the first cycle, and the capacity is decreased to only 165.9 mA h g −1 after 87 cycles. The reason for the large difference in capacities for CoFeP and FeP is that the Co doping into FeP boosts the electronic conductivity of electrode, and the unique hollow structure affords more active sites and provides a faster kinetics . Figure b shows the rate capabilities of the FeP and CoFeP electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…21,22 Al 2 O 3 and MgO particles have been introduced into doped ceria electrolytes as the second phase to enhance the mechanical properties. 11,[23][24][25] A improvement in fracture toughness has been reported in 80% (Ce 0.8 Gd 0.2 )O 2Àd + 20%AlO 1.5 composite. 26 Whereas, the excessive addition of Al 2 O 3 and MgO exhibits a detrimental effect on the conductivity as they are blocking phases for oxygen ion conduction.…”
Section: Introductionmentioning
confidence: 93%
“…It is reported that the flexural strength and fracture toughness of CeO 2 are only about 100 and 1.5 MPa·m 1/2 , respectively, whereas the gadolinium‐doped ceria (GDC) shows an improved mechanical property, the flexural strength of 175 ± 10 MPa, and the fracture toughness (K IC ) of 1.75 ± 0.3 MPa·m 1/2 . Al 2 O 3 and MgO particles have been introduced into doped ceria electrolytes as the second phase to enhance the mechanical properties . A improvement in fracture toughness has been reported in 80% (Ce 0.8 Gd 0.2 )O 2−δ + 20%AlO 1.5 composite .…”
Section: Introductionmentioning
confidence: 99%
“…[3,4], transparent ceramics [5], humidity sensors [6], insulating materials in fusion reactors [7], dye adsorbents [8], luminescent hosts [9], ceramic ultrafiltration membranes [10], infrared window materials in optical devices [11] and catalyst support for n-butane dehydrogenation [12], oxidative dehydrogenation of ethane with CO 2 [13], methane oxidation [14], methane steam-reforming [15], ammonia decomposition [16], liquid phase citral hydrogenation [17], propane dehydrogenation [18], Methane decomposition [19], methane dry reforming [20], selective hydrogenation of acetylene [21], butane steam reforming [22] and autothermal reforming of methane [23]. MgAl 2 O 4 spinel was synthesized by metalechitosan complexation [1], hydrothermal [13], high-energy ball milling (mechanochemical synthesis) [2,24], solid state reaction (ceramic method) [2], co-precipitation [2,25], microwave-assisted combustion [26], solegel [27,28], organic precursor [28], combustion [28,29], surfactant assisted precipitation [30], modified solegel [31,32], spraydrying [33], freeze-drying [34], microwave-assisted solution combustion [35], normal micelle micro-emulsion …”
Section: Introductionmentioning
confidence: 99%